OLD AND NEW: PELUANG DAN TANTANGAN ALUMNI KOMUNIKASI PENYIARAN ISLAM DI DUNIA MEDIA - Anita Trisiah; Mu’minatul Hasanah Mokhtar (Wardah, 2018)
This research entitled Old and New: Opportunities and Threats for Alumni of Islamic Broadcasting Communication in Media is conducted due to the development of media, both printed and electronics and online as well which asked a high competency for those who work within. To know how the opportunities and threats for the alumni and how the study program playing its role to form an Islamic Journalists, the researcher will analyze the research qualitatively based on data collected through interview, observation and documentation. The result of this research are the opportunities alumni should take through increasing their competency as a professional journalist which include awareness of ethics, law and career, knowledge of communication and reporting skill, using devices, research, investigation and information technology. Those opportunities should be taken up because challenges never been so easy. The media needs a high skilled journalist to get things done. Keywords: competency, journalist, mass media